China-Britain-Uganda: Trilateral Development Cooperation in Agriculture - Hang Zhou (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2018)
Trilateral development cooperation is believed to reflect aid's changing geographies while helping to forge new, more equitable partnerships. Chinese engagement in trilateral development cooperations has so far received limited attention, and this paper by Hang Zhou seeks to fill the gap. By drawing on field research from one of China's first trilateral projects with traditional donors in Africa—a Ugandan cassava project co-initiated with Britain—this paper details key coordination challenges from the project implementation phase. More importantly, it also critically examines two often-claimed "advantages" of trilateral development cooperation: its contribution to more horizontal development partnerships and its role in providing recipient countries with more suitable technical assistance.
Keywords: 330